Chapters from Life of Tibetans - Martin Hanker (Karolinum Press, 2019)
The e-book Chapters from life of Tibetans was written by master and doctoral students of Tibetan Studies as a short overview and tool for bachelor students encountering the Tibetan cultural milieu for the first time, offering insight into Tibetan culture. It summarises the life of Tibetans from birth to death, focusing on important matters of Tibetan culture. Over the course of eleven chapters, the e-book describes childbirth, upbringing, rites of passage (including weddings), family life, work, amusement, examples of annual and religious rituals and death (including funerals). Apart from that, the e-book introduces readers to important Tibetan terminology and recommends literature for further reading on Tibetan subjects.